Young women's carceral geographies : abandonment, trouble and mobility - Schliehe, Anna (Emerald Publishing Limited, 2021)
Young women are a group often neglected even in feminist scholarship. Interrogating conceptual ideas around power, punishment and abandonment with specific reference to the experience of young women, this book examines the particular challenges that young women face within the criminal justice system, and traces their journeys in, out and beyond confinement. Contributing ethnographic insights from multiple sites of incarceration to explore how secure care, prison and closed psychiatric facilities impact on young women's lives, Schliehe's study goes further than individual carceral spaces by delving into the wider context of young women's journeys through different types of institutional spaces and beyond. The exploration of these journeys challenges and re-develops our understanding of extreme mobility, and showcases how this can lead to the abandonment of a group of young people who live on the margins of social and legal norms. Merging theoretical and empirical findings to highlight how age and gender matter in discourses on crime and justice, Schliehe demonstrates how we have to look beyond institutions to understand confinement in our age of prison crisis, austerity and marginalization. Curating findings from across human geography and criminology, this book fills an important gap in the literature, offering up essential reading for practitioners and researchers interested in gender, age and confinement.
Includes index.
Keywords: Young women -- Effect of imprisonment on.; Women prisoners.; Social Science -- Penology.; Prisons.; elektronické knihy; electronic books